Penerapan Produk Wisata yang Berkelanjutan di DIY dalam Menyongsong Abad Samudra Hindia - Kiswantoro, Amin; Irawati, Novi (Sekolah Tinggi Pariwisata AMPTA, 2020)
The southern coast of Yogyakarta, is one area that has the potential to be developed as sustainable tourism in DIY, such as Parangtritis Beach, Glagah Beach and Baron Beach. This article discusses the system of processing sustainable tourism products that exist in the southern region of DIY in order to become leading tourism in welcoming the Indian Ocean Century. Research has been conducted using descriptive methods with a qualitative approach. Data collection was carried out using observation and interviews with Tiagulation analysis techniques and SWOT analysis. The results show that Parangtritis Beach is superior to Glagah Beach and Baron Beach in terms of developing attractiveness, facilities and accessibility. In addition, the relationship between the partnership pattern between the government and the tourism industry is very well coordinated and community empowerment is also seen as a mobilizer. Tourism product development, partnership patterns and community empowerment at Baron Beach have been carried out effectively and sustainably. Whereas in Glagah Beach, the processing of tourism products has experienced many obstacles, due to the construction of Yogyakarta's new airport which has an impact on the condition of tourism products as well as a shift in land use from the center of agro-tourism activities to the new airport area and lack of attention from the local government.